DEEP ORGANIZATIONAL CULTURE IMPROVE EMPLOYEE PERFORMANCE - Indri Yani; Ika Widiastuti (Perkumpulan Dosen Program Hibah Indonesia, 2023)
Organizational culture is an important element in the development and progress of organizations both in the business world, government, educational institutions and social religious organizations. This research aims to describe organizational culture through theoretical analysis and empirical analysis. The study is divided into three parts. First, an introduction which outlines issues related to culture. Second, the discussion describes the opinions of experts supported by empirical information. Third, the conclusion is a conclusion of the problems and discussions that have been described. The conclusion from this research is that the development and existence of an organization has a strong and significant relationship with organizational culture